SPIRITUAL DIMENSIONS OF UKRAINIAN EXISTENCE IN PROSE BY YURII TYS (BASED ON THE COLLECTION «THE SYMPHONY OF THE EARTH») - Залевська, І. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article on the material of the collection «The Symphony of the earth» analyzed national and spiritual issues of creativity by Yurii Tys, considered peculiarities of the author’s artistic thinking, focused attention on the problems of the restoration of Ukrainian statehood, examined the specificity of artistic modeling of belletristic reality of the writer’s historical prose.